1985
DOI: 10.1111/j.1524-4725.1985.tb02976.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemosurgical Reports: Basal‐Cell Carcinoma Resulting from Radiation Therapy for Hypertrophic Tonsils

Abstract: Benign dermatologic conditions are no longer treated with therapeutic radiation because of the late complications that can result. One of the most serious complications that may occur is the development of skin cancer of various types. In this report, a patient received radiation for hypertrophic tonsils and later developed basal-cell carcinomas in the irradiated areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Until the 1960s, the use of superficial radiation for benign skin disease was quite common 8 . Low‐dose radiation was a popular therapy for tinea capitis until the introduction of the effective antifungal agent griseofulvin in 1959 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Until the 1960s, the use of superficial radiation for benign skin disease was quite common 8 . Low‐dose radiation was a popular therapy for tinea capitis until the introduction of the effective antifungal agent griseofulvin in 1959 9 .…”
Section: Discussionmentioning
confidence: 99%
“…These neoplasms can even arise on radiated areas where there is no sign of chronic radiation damage. The latency period for the development of a skin cancer after irradiation is variable, ranging from 4 to 40 years with an average of 20 years 1 …”
Section: Discussionmentioning
confidence: 99%
“…Data from retrospective studies covering a large number of patients treated with radiotherapy for tinea capitis showed that radiation with low doses induced the development of basal cell carcinoma (BCC) more frequently than SCC 6–8 . Several case reports mentioning the development of multiple BCCs following low‐dose radiation therapy for some other benign diseases like hypertrophic tonsils, acne vulgaris, atopic dermatitis, and hyperthyroidosis also support this issue 1,9,10 …”
mentioning
confidence: 97%
See 2 more Smart Citations